Global political economy evolution and dynamics - O'Brien, Robert; Williams, Marc (Palgrave Macmillan, 2007)
The book is theoretically informed but, unlike many books in its field, it introduces a range of approaches and shows how these can be applied and how useful they are in tackling key issues from trade, production, and finance to social divisions, development, and the environment.